2021
DOI: 10.3390/rs13040598
|View full text |Cite
|
Sign up to set email alerts
|

Red-Green-Blue and Multispectral Imaging as Potential Tools for Estimating Growth and Nutritional Performance of Cassava under Deficit Irrigation and Potassium Fertigation

Abstract: Cassava has high energy value and rich nutritional content, yet its productivity in the tropics is seriously constrained by abiotic stresses such as water deficit and low potassium (K) nutrition. Systems that allow evaluation of genotypes in the field and greenhouse for nondestructive estimation of plant performance would be useful means for monitoring the health of plants for crop-management decisions. We investigated whether the red–green–blue (RGB) and multispectral images could be used to detect the previs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
1
8
0
2
Order By: Relevance
“…It was possible to predict the height of this crop with high performance (R 2 = 0.79) using model I. Recent studies [2,17] reported similar results for beans and cassava crops, respectively, demonstrating the utility of UAVs and vegetation indices for the compilation of biometric variables. The use of these tools becomes more important due to the need to conduct more agronomic evaluations in a timely manner in crops and mainly in those that are cultivated in arid environments such as the Peruvian coast.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It was possible to predict the height of this crop with high performance (R 2 = 0.79) using model I. Recent studies [2,17] reported similar results for beans and cassava crops, respectively, demonstrating the utility of UAVs and vegetation indices for the compilation of biometric variables. The use of these tools becomes more important due to the need to conduct more agronomic evaluations in a timely manner in crops and mainly in those that are cultivated in arid environments such as the Peruvian coast.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, other researchers, predicted aerial biomass in various crops such as sunflower, corn and wheat [13][14][15][16]. Similarly, in Kenya RGB images were used to estimate growth and nutritional yield of cassava [17]. Since evaluations are necessary during the development of crops and as beans are one of the main foods in the basic family basket, it is essential that research is conducted to guarantee food security under the context of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for implementing rapid phenotyping based on digital images for TCC prediction was demonstrated in this study. In addition, image analysis allows the analysis and incorporation of other characteristics of agronomic importance in cassava cultivation, such as the evaluation of canopy and root yield-related traits, assessment of the linkage between root architecture and micronutrient (zinc and calcium) concentration, and estimation of the growth and nutritional performance of cassava under poor irrigation and potassium fertigation [ 51 53 ]. Therefore, these variables can be used in the composition of multi-trait selection indexes for further optimization of cassava breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Formula yang didapatkan untuk estimasi K pada tanaman y = 1,8003 + (0,5716*NDVI CS). Menurut Wasonga et al, (2021), penggunaan NDVI dapat memperolah pendugaan yang akurat karena mengamati melalui klorofil daun. Nilai NDVI tinggi ditunjukkan pada tanaman dengan irigasi penuh yang menandakan tanaman tersebut mengandung klorofil yang tinggi sehingga dapat dikatakan tanaman yang sehat.…”
Section: Model Estimasi K Dengan Indeks Vegetasiunclassified